The Law on partnerships and private corporations : for business students - Suarez, Carlos B.; Suarez, Alexander Q. (Manila, Philippines : Philippines GIC Enterprises & Co., Inc., 2014)
The format of the book is presented in a capsule outlined style and the notes, comments, examples and illustrative cases are preceded by headings systematically arranged purposely to aid students in Partnership and Corporation Laws who will be introduced for the first time in the "World of Law". This book therefore, is the response of a continuing obligation on the part of the authors as reviewers in Commercial Law, to present the law clearly so that it could be easily understood and never were their intention to compete with other authors but only to explain.
Title IX - Partnerships -- General Provisions 1 -- Obligations of the Partners 29 -- Dissolution and Winding Up 88 -- Exercises in Contract of Partnership Including Past CPA Examination Questions 144 br> The Corporation Code of the Philippines (Batas Pambansa Blg. 68) Title I - General Provisions 170 -- Title II - Incorporation and Organization of Private Corporations 199 -- Title III - Board of Directors/Trustees/Officers 233 -- Title IV - Powers of Corporations 262 -- Title V - By - Laws 296 -- Title VI - Meetings 305 -- Title VII - Stocks and Stockholders 332 -- Title VIII - Corporate Books and Records 363 -- Title IX - Merger and Consolidation 370 -- Title X - Appraisal Right 378 -- Title XI - Non-Stock Corporations 385 -- Title XII - Close Corporations 392 -- Title XIII - Special Corporations 406 -- Title XIV - Dissolution 418 -- Title XV - Foreign Corporations 429 -- Title XVI - Miscellaneous Provisions 446 -- Exercises in Corporation Law Including Past CPA Examination Questions 454
Keywords: PARTNERSHIP -- PHILIPPINES